Aménagement d’ossuaires dans le baptistère paléochrétien de Brioude (Haute-Loire) : sélection, tri des ossements et relation À l’Âge au décès - Aline Thomas; Fabrice Gauthier; Esther Gatto; Pascal Murail (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The baptistery of Brioude is today a unique monument in Auvergne. It was associated with the sanctuary housing the relics of Saint Julien, which dates to the early Middle Ages. During its period of use, the baptistery provided for intra muros burial. This is a unique occurrence in Merovingian Gaul.Two phases of funerary use could be identified from the regularity with which the remains had been treated. The first, dating from the 6th century AD, is contemporary with the use of the baptistery. The second dates from the middle of Merovingian period (from the 7th century A.D.) and is associated with the building of a new structure on the site of the baptistery. This structure was accompanied by burials placed directly over those of the previous phase. The analysis of spatial relationships among burials enabled us to identify a transitional stage between these two phases. This stage was identified on the basis of the disturbance of several burials belonging to the first phase, subsequent to the construction of the structure of the second phase. These disturbances led to the displacement of partial destruction of some sarcophagi and the inclusion of some disturbed skeletal remains in ossuaries.Three ossuaries have been discovered under the floor of the baptistery. The identification of osteological relations of the second order among these different groups demonstrates that, first, the three ossuaries resulted from a single action and, second, the distribution of skeletal elements was not random but that selection and sorting of adult bones had been carried out according to their anatomical type (long bones, cranium, small and middle-sized bones), and these had been separated into three different deposits. Furthermore, we noted that paired immature skeletal elements were divided between two ossuaries. Finally, the age assessment of these young individuals classified them into the 5-9 age category, a group that was absent from the rest of the burial area. These results lead us to hypothesize that there had once been a burial area reserved for this part of the population. This area seems to have been destroyed during the construction of the second phase structure.